Blood-Glucose Lowering Effect Of Swietenia Macrophylla Seed Extratcts In Normal And Streptozotocin-Induced Diabetic Rats - Hashim, Mohd Akmal (2012)
Swietenia macrophylla (meliaceae) seeds have been used in folklore for treating various diseases including diabetes. The aim of the present work was to investigate the antidiabetic activity of the plant extracts and determine the active compound(s) that might contribute to the activity. Pulverized, dried powder of S. macrophylla seeds was extracted serially with petroleum ether, chloroform, methanol and water by two different methods; Soxhlet extraction and maceration methods. The extracts obtained were examined for hypoglycaemic activity in normal rats, inhibition of the rise of blood glucose level in intraperitoneal glucose tolerance test (IPGTT) and antihyperglycaemic activity in streptozotocin-induced diabetic rats. It was found that all the extracts obtained from Soxhlet method did not possess antidiabetic activity. As for the extracts obtained from the maceration method, none of the extracts lowered the blood glucose levels in hypoglycaemic test in normal rats. However, petroleum-ether and aqueous extracts obtained by maceration method significantly inhibited the rise of blood glucose levels in IPGTT. In streptozotocin-induced diabetic rats, only aqueous extract at 3,5 and 7 hours after administration reduced the blood glucose level. Twice daily oral administration of aqueous and petroleum-ether extracts to diabetic rats showed that only aqueous extract (1000mg/kg/daily) significantly decreased the fasting blood glucose levels after 14 days treatment. The aqueous extract of S. macrophylla seeds was then fractionated with chloroform, ethyl-acetate and n-butanol.